A comparative study of flow boiling performance in the interconnected microchannel net and rectangular microchannels. (July 2016) - Zhang, Shiwei; Tang, Yong; Yuan, Wei; Zeng, Jian; Xie, Yingxi
Highlights: IMN yields higher HTC and lower pressure drop at low to medium mass fluxes. IMN conspicuously suppresses the two-phase instability at low to medium mass fluxes. Mitigation of two-phase instability leads to higher HTC and lower pressure drop. HTC changes in line with the flow pattern transition from nucleate to convective boiling. Abstract: An interconnected microchannel net (IMN) was developed using microfabrication technique for flow boiling heat transfer enhancement. The flow boiling experiments were conducted using deionized water as the working fluid with variation in the heat flux and mass flux ( G  = 100, 180 and 250 kg m −2  s −1 ) and a comparison with conventional rectangular microchannels (RMC) was investigated. The results indicated that the IMN yielded higher heat transfer coefficient and lower pressure drop at G  = 100 and 180 kg m −2  s −1 than that of the RMC. However, a reverse trend was observed at G  = 250 kg m −2  s −1 . A transition of boiling mechanism from the nucleate boiling region to the convective boiling region occurred with increase of vapor quality for both samples at G  = 180 and 250 kg m −2  s −1 accompanied with the flow pattern changing from the bubbly flow to annular flow, which didn't occur at G  = 100 kg m −2  s −1 . Further study revealed that the advantage of mitigating the two-phase flow instability for the IMN diminished as mass flux increased to G  = 250 kg m −2  s −1 . Such phenomenon may account for the lower heat transfer rate and higher pressure drop for the IMN than that for the RMC at high mass flux.